The Impact of Random Noise on the Dynamics of COVID-19 Epidemic Model - Amine El Koufi; Nouhaila El Koufi; Abdelkrim Bennar; Namana Seshagiri Rao (Journal of Applied Mathematics)
At the end of 2019, the world knew the propagation of a new pandemic named COVID-19. This disease harmed the exercises of humankind and changed our way of life. For modeling and studying infectious illness transmission, mathematical models are helpful tools. Thus, in this paper, taking into account the effect of the intensity of the noises, we define a threshold value Πs of the model, which determines the extinction and persistence of the COVID-19 pandemic. We give numerical simulations to illustrate the analytical results.